Advances in Nanotechnology for the Management of Coronary Artery Disease - Rhee, June-Wha (2012)
Nanotechnology holds tremendous potential to advance the current treatment of coronary artery disease. Nanotechnology may assist medical therapies by providing a safe and efficacious delivery platform for a variety of drugs aimed at modulating lipid disorders, decreasing inflammation and angiogenesis within atherosclerotic plaques, and preventing plaque thrombosis. Nanotechnology may improve coronary stent applications by promoting endothelial recovery on a stent surface utilizing bio-mimetic nanofibrous scaffolds, and also by preventing in-stent restenosis using nanoparticle-based delivery of drugs that are decoupled from stents. Additionally, nanotechnology may enhance tissue-engineered graft materials for application in coronary artery bypass grafting by facilitating cellular infiltration and remodeling of a graft matrix.